Dynamic Disorder Restriction of Methylammonium (MA) Groups in Chloride-Doped MAPbBr 3 Hybrid Perovskites: A Neutron Powder Diffraction Study - Lopez, Carlos Alberto (2019)
The hybrid methylammonium (MA) lead halide MAPbX 3 perovskites present an appealing optoelectronic behavior with applications in high-efficiency solar cells. The orientation of the organic MA units may play an important role in the properties, given the degrees of freedom for internal motion of MA groups within the PbX 6 network. The present neutron powder diffraction study reveals the dynamic features of the MA units in the hybrid perovskite series MAPb(Br 1−x Cl x ) 3 , with x=0, 0.33, 0.5, 0.67, and 1. From difference Fourier maps, the H and C/N positions were located within the PbX 6 lattice; the refinement of the crystal structures unveiled the MA conformations. Three different orientations were found to exist as a function of the chlorine content (x) and, therefore, of the cubic unit-cell size. These conformations are stabilized by H-bond interactions with the halide ions, and were found to agree with those reported from theoretical calculations.